Impacto de las redes sociales en los establecimientos de restauración de la ciudad de Babahoyo - Leon Franco, Genesis Odethe (2023)
This project consists of answering the research question: What is the impact of the use of social networks in catering establishments in the city of Babahoyo? The main objective is to analyze the impact of the virtual platforms used by these establishments, to determine promotional strategies, increase sales and generate competitiveness in the food and beverage sector. Through mixed research, it was possible to obtain qualitative and quantitative data that allowed knowing the perception of the owners of food and beverage establishments in the city of Babahoyo regarding the impact generated by the management of social networks for said establishments. Data that were collected through a non-probability sample for convenience through a survey of 25 study subjects, an observation sheet made to 6 establishments chosen for being crowded, and an interview with the owner of the establishment that, according to the results, It reflects better management of the different virtual platforms, which allowed us to know their perception of how social networks influence customers. Coming to the conclusion that according to the management and importance given to social networks, these can serve as a communication channel to strengthen the presence of the establishment and the impression that users have of it. Among the main impacts are the increase in customers, a greater number of sales, therefore, improvement in business profitability, market positioning, and spaces for interaction with the community. It is recommended that the owners of catering establishments keep their social network profiles updated and attractive, hire professionals to manage their social networks, present meaningful content for customers that helps build loyalty and build trust, present specific information, upload images of the products so that the customer is satisfied at the moment of truth, as well as estimating the response time because users generally monitor the networks at the same time they want to consume.